Determinants of Impulse Buying in Buy Now Pay Later Users - Yuliani, Rizka (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to gain new knowledge and analyze the effect of financial socialization, financial literacy, and financial self-efficacy on Pay Later users. This study also examines the mediating role of financial self-efficacy between financial socialization and impulse buying among Pay Later users. This research was conducted among the Millennial Generation and Generation Z over eight months, from October 2023 to June 2024. The method used is a questionnaire survey with a population of Millennials and Generation Z who use Pay Later. The sampling technique employed is the convenience sampling method, using the Cochran formula to select 143 respondents. The research analysis technique uses Structural Equation Modeling (SEM) with Analysis of Moment Structures (AMOS) software. The purpose of using this application is to measure the levels of validity and reliability by combining the variables in the study.